ANALISIS FINANSIAL HASIL HUTAN BUKAN KAYU (HHBK) KARET DAN DURIAN DI KABUPATEN SIAK - Insusanty, Enny; Ratnaningsih, Ambar Tri; Prastyaningsih, Sri Rahayu (Wahana Forestra: Jurnal Kehutanan, 2017)
Non-Timber Forest Products (NTFPs) are part of an ecosystem that has diverse roles both for the natural environment and for humans. NTFPs that are commonly used and commercialized include sandalwood, sap, gaharu, sago, rattan, aren, bamboo, medicinal plants and fruit plants. The purpose of this research is to perform financial analysis and feasibility of HHBK especially rubber and durian. The method used is survey method with purposive sampling to rubber farmer and durian in Siak Regency. The analysis of research data is descriptively qualitative. The results showed that rubber value of NPV Rp 7.076.819.809, -, BCR 2.24 and IRR 15.09% while durian has NPV Rp 738.553.324, - BCR 2.00 and IRR 13.67%. Based on the criteria of financial feasibility indicators can be concluded that the rubber cultivation and durian business financially feasible to be developed.